The relationship between perceptions toward advertising and consumption of energy-dense nutrient-poor foods among adults in the United States: results from a national survey - Thai, Chan L.; Villarreal, Jacqui; Thai, Jacqueline A. (Frontiers in Public Health, 2025)
IntroductionMuch of the research on the effects of food advertising has been focused on children and adolescents; however, adults may also be influenced. Prior research has also shown that exposure to food advertisements have impacted the consumption behaviors of adults. The purpose of this study is to explore (1) the differences in perceptions toward and trust in food advertisements between racial/ethnic population subgroups; and (2) the associations between perceptions toward food advertising and the consumption of energy-dense, nutrient poor (EDNP) foods among adults using data from a national data set (n = 1,535).MethodsData from the National Cancer Institute’s Family Life, Activity, Sun, Health, and Eating (FLASHE) survey were utilized in this secondary data analysis study. We conducted one-way ANOVAs to evaluate demographic subgroup differences within advertising trust and perceptions, and utilized bivariate and multivariable linear regression models to examine associations between (1) the perceptions toward and trust in food advertisements between racial/ethnic population subgroups; and (2) the associations between perceptions toward food advertising and the consumption of EDNP foods, while controlling for sociodemographic factors.ResultsResults show significant differences between racial/ethnic groups on advertising perceptions (F = 8.59, p < 0.0001). Planned contrasts show that there was a statistically significant and meaningful difference (p = 0.04) between Non-Hispanic Blacks (mean = 2.85) and Non-Hispanic Whites (mean = 2.52) for trust in food advertising. Regression analyses show that as positive perceptions toward food advertising increase among adults, there is an increase in daily frequency of consumption of EDNP foods and drinks (𝛽 = 0.15, p < 0.0001). This pattern was similar for trust in food advertising (𝛽 = 0.13, p < 0.0001).DiscussionGiven that previous studies have shown that ethnic minority groups, particularly Non-Hispanic Blacks, are more likely to be exposed to unhealthy food advertisements across various types of media, such as TV, billboards, and in grocery stores, it is possible that Non-Hispanic Black adults have greater trust in food advertising because of the increased environmental exposure to advertising through various channels of communication. Numerous studies have demonstrated that exposure to food advertisements is linked to consumption of the foods found in those advertisements. Our results provide some initial empirical support for the cognitive mechanisms of how exposure to food advertising may contribute to consumption. Developing advertising literacy interventions to inoculate against the cognitive impacts of food advertising may be a viable strategy to limiting consumption of EDNP foods.